Martial arts and combat sports in School Physical Education: Philosophical-Educational Inteface in the student perpective (Research, Society and Development, 2021)
Incluir o resumo em inglês. Qualitative investigations applied to Martial Arts and Combat Sports (MA&CS) are spreading in the academic-scientific environment. This study aimed to verify the students' perception regarding their most relevant learning about Martial Arts and Combat Sports, after being subjected to pedagogical practices in school Physical Education classes. 150 students in the 3rd year of high school participated, in Pinheiro (MA). Participants presented the Free and Informed Consent Form (FICF) signed by a responsible person and filled out the questionnaire to enter the study. Only the volunteers who attended (75%) of the 12 proposed classes reached the end and completed the questionnaire again. The contents covered were related to the modalities of Judo, Jiu-Jitsu, Sumo, Greco-Roman and Huka-Huka (grappling fights); Boxing, Capoeira, Karate, Muay-Thai and Taekwondo (touch fights); and Sword, with Saber, Sword and Foil Sword (fights with implements), which were approached based on the attitudinal, conceptual and procedural dimensions, pointed out by Coll (2000). After collecting the pre- and post-intervention data, we adopted Content Analysis (Bardin, 2011) for categorical analysis and, subsequently, planning and use of the Software Statistical Package for the Social Sciences (SPSS), version 24.0, IBM, 2016. The Chi-square Test sought to identify significant differences in the results obtained and in all evaluations, the Confidence Interval (CI=95%) was considered, with significance level (p = 0.05). The results revealed a drop in the percentage of students (38%, n = 57), who pointed out as their main learning “to know blows” and “to know how to defend themselves”. New assertions emerged as the most significant learning “knowing new cultures” (33.4%, n = 51), “knowing new philosophies” (28%, n = 46) and “differentiating brawls from fights” (15.3%, n = 22). The study brought positive responses on the theme MA&CS in the school context, however, there is a lack of new research in this aspect and in different school years and perspectives.